Incidence and risk factors for sport-related concussion in female youth athletes participating in contact and collision invasion sports: a systematic review - Ernst, L.; Farley, J.; Milne, N. (Sports Medicine, 2025)
Background: The incidence and risk factors for sport-related concussion (SRC) associated with contact and collision invasion sports (CCIS) in female youth are unclear. Objectives: This systematic review aimed to identify (i) the incidence of and (ii) risk factors for SRC in female youth athletes playing CCIS. Methods: A systematic search of PubMed, CINAHL, Embase, SPORTDiscus and ProQuest to 8 May, 2024 was conducted. Two reviewers independently screened articles against eligibility criteria and assessed risk of bias (Joanna Briggs Institute Critical Appraisal Tool). Aetiological or intervention studies reporting on SRC incidence or risk factors in female youth athletes (aged 13-19 years and under) participating in CCIS were included. Meta-analyses were conducted to explore SRC incidence and risk factors. For each meta-analysis of SRC incidence rate, sub-group analyses were conducted by sport. Where heterogeneity was above 60% for the meta-analysis of SRC risk/protective factors, sensitivity analyses were conducted. Results: The search yielded 4509 articles; 66 were included. Sport-related concussion incidence or risk factor data for nine CCIS were extracted. Pooled estimates revealed SRC incidence for female youth athletes in CCIS combined was 0.50/1000 match and practice hours (95% confidence interval [CI] 0.34-0.66). When examined by sport classification, SRC incidence in contact invasion sports was 0.12/1000 match and practice hours (95% CI 0.03-0.21), and in collision invasion sports was 2.08/1000 match and practice hours (95% CI 0.90-3.25). Sub-group analysis by individual sport revealed female youth soccer players had the highest overall SRC incidence rate (0.89/1000 match and practice hours, 95% CI - 0.19 to 1.97) amongst contact sports, and rugby union players had the highest overall SRC incidence rate (4.04/1000 match and practice hours, 95% CI 3.03-5.05) among collision sports. Forty-five studies (68%) reported SRC risk factor data, investigating 12 different potential risk factors. Female youth sustained over 7.5 times the rate of SRC in matches compared with practice (incidence rate ratio 7.52, 95% CI 6.32-8.95, p < 0.01) when competing in CCIS; however, considerable heterogeneity existed (I2 = 84.98%). When exploring potential risk factors, no significant difference was found in SRC rate between female youth lacrosse players wearing versus not wearing headgear (p = 0.07). No significant difference was found in SRC rates between female youth athletes competing in younger versus older age groups (incidence rate ratio 0.91, 95% CI 0.52-1.61, p = 0.48, I2 = 0.00%). Insufficient evidence was available to examine remaining risk factors. Conclusions: This meta-analysis revealed SRC in female youth playing CCIS was higher than previously reported, with SRC rates higher in matches than practice. Soccer had the highest SRC incidence rate for female youth athletes competing in contact invasion sports, whilst rugby union demonstrated the highest SRC incidence rates for collision invasion sports. The results of this review should be interpreted with caution given the lack of representation from some common CCIS codes. Further research is required to examine SRC risk factors in female youth athletes participating in CCIS.